2006
DOI: 10.3998/ark.5550190.0007.a11
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of quinoline alkaloids: 4-Methoxy-1-methyl-2-quinolinone and its analogs

Abstract: The microwave-induced synthesis of some quinoline alkaloids of the type 4-methoxy-1-methyl-2-quinolinone including folimine is reported. The precursors 4-hydroxy-2-quinolinone derivatives were effectively prepared in a single step from aniline and diethylmalonate using ptoluenesulfonic acid as a catalyst and these intermediates were converted to the titled quinoline alkaloids by treatment with dimethyl sulfate, N,N-dimethylformamide and potassium carbonate. The presented synthentic procedure is a convenient, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Isoxazolo[2,3-c][1,3,5]thiadiazepin-2-ones 4 exhibited characteristic absorption bands at 1680 and 1620 cm −1 due to C=O and C=N functional group stretching vibrations respectively. 1 H NMR spectra of 4 displayed to prominent singlets at δ 4.27 and 5.50 due to CH 2 and NCHAr proton respectively confirming the cyclization 13. C NMR spectra of 4 is consistent with the proposed structure by displaying the absorption peaks at 39.57, 66.05, 160.32 and 193.47 due to CH 2 , NCHAr, C=N and C=O carbons respectively.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Isoxazolo[2,3-c][1,3,5]thiadiazepin-2-ones 4 exhibited characteristic absorption bands at 1680 and 1620 cm −1 due to C=O and C=N functional group stretching vibrations respectively. 1 H NMR spectra of 4 displayed to prominent singlets at δ 4.27 and 5.50 due to CH 2 and NCHAr proton respectively confirming the cyclization 13. C NMR spectra of 4 is consistent with the proposed structure by displaying the absorption peaks at 39.57, 66.05, 160.32 and 193.47 due to CH 2 , NCHAr, C=N and C=O carbons respectively.…”
supporting
confidence: 71%
“…1 H NMR spectra were recorded on a Varian Gemini 300 MHz spectrometer. 13 C NMR spectra were recorded on a Bruker 75 MHz spectrometer. Chemical shift values are given in ppm (δ) with tetramethyl silane as internal standard.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Kemnitzer et al [13] found a new series of apoptosis inducers, the 1-benzoyl-3cyanopyrrolo [1,2-a]quinolines (Formula I), among which the compound 1-(4-(1H-imidazol-1yl)benzoyl)-3-cyanopyrrolo[1,2-a]quinolone (Formula II) displayed high cytotoxic activity in T47D human breast cancer, HCT-116 human colon cancer cells and SNU398 hepatocellular carcinoma cells. 2-quinolone derivatives have been shown to have antitumor, antimalarial, antiviral, antioxidant, antidepressant, cardiac stimulant, and anti-asthmatic biological activity [14][15][16][17][18][19][20][21][22][23][24]. Quinoline is a scaffold with pharmacological value spread in a variety of synthetic and natural compounds that are bioactive [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have synthesised a series of hydroxyl-quinolone derivatives and used them as precursors to prepare some novel azo disperse dyes. [13][14][15] As a part of our ongoing efforts towards the synthesis of 4-hydroxyquinolin-2(1H)-one derivatives, 16,17 we have synthesised 4-hydroxybenzo[h]quinolin-2-(1H)-one (Scheme 1) and prepared some new 4-hydroxyquinolin-2(1H)-one derivatives (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%